1979
DOI: 10.1111/j.1365-2621.1979.tb06458.x
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Meat Pieces: An Investigation of the Use of Myosin‐containing Extracts From Pre‐ and Post‐rigor Bovine Muscle as Meat Binding Agents

Abstract: The feasibility of using myosin, extracted from post-rigor bovine muscle, as a binding agent for meat pieces, was examined. Crude myosin was extracted with solutions containing various concentrations of sodium chloride (salt) and sodium tripolyphosphate (TPP). Maximum yield was obtained using 1M salt and about 0.25% TPP in the extracting solution. Binding strength, i.e. the strength with which pieces of meat adhere, of crude myosin extracted with 1M salt and 0.15, 0.25 or 0.5% TPP were not significantly differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1983
1983
2004
2004

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…1. Solubility (6) of myosin was recorded in 0.2 M KCl. Actin-activated Mg 2 + -ATPase activity (0) was determined at 25°C in a medium containing 0.5 mg/ml myosin, 0.2mg/ml actin, 30mM KCI, 20mM Tris-HCI buffer (pH 7.5), 1mM ATP and 1mM MgCI 2 • EDTAATPase (.)…”
Section: Effects Of Actin Atp and Inorganic Pyrophosphatementioning
confidence: 99%
See 1 more Smart Citation
“…1. Solubility (6) of myosin was recorded in 0.2 M KCl. Actin-activated Mg 2 + -ATPase activity (0) was determined at 25°C in a medium containing 0.5 mg/ml myosin, 0.2mg/ml actin, 30mM KCI, 20mM Tris-HCI buffer (pH 7.5), 1mM ATP and 1mM MgCI 2 • EDTAATPase (.)…”
Section: Effects Of Actin Atp and Inorganic Pyrophosphatementioning
confidence: 99%
“…Freshly prepared myosin (5mg/ml) in 0.6M KCI and 5mM Tris-maleate buffer (pH 6.5) was incubated at 25°C before each measurement. Fluorescence (0) and light scattering intensity (6) were determined at 25°C in. a medium containing 0.5 mg/ml of myosin, 0.6 MKCI, and 5 mM Trismaleate buffer (pH 6.5).…”
Section: Effects Of Actin Atp and Inorganic Pyrophosphatementioning
confidence: 99%
“…Salt-soluble myofibrillar proteins participate in similar binding reactions at the junction between meat particles or sectioned muscles (Schnell et al, 1970;Acton, 1972a;Macfarlane et al, 1977;Schmidt and Trout, 1982). The binding strength developed at the junction between meat pieces is affected by vacuum (Maesso et al, 1970;Turner et al, 1979;Solomon and Schmidt, 1980;Wiebe and Schmidt, 1982). Thermal energy input during cooking is also required for crosslinking in film-to-meat adhesion and meat-to-meat binding Acton, 1972b;Acton and Dick, 1984;Terlizzi et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…It was not until recently, however, that scientific evidence was obtained to actually show the importance of "actomyosin" in the binding of meat pieces, Siege1 and Schmidt (1979) prepared crude myosin fractions and found that the binding ability of the crude myosin fractions was greater than a muscle homogenate free of f a t and sarcoplasmic proteins, a total muscle homogenate or a nonprotein control consisting of salt, phosphate and water. Turner et al (1979) found that crude myosin extracted from post-rigor bovine muscle had a binding strength only slightly lower than myosin extracted from pre-rigor muscle. Galluzzo and Regenstein (1978) used myosin, actin and synthetic actomyosin (SAM) extracted from chicken breast muscle.…”
mentioning
confidence: 86%